Early Miocene Mollusca from McMurdo Sound, Antarctica (ANDRILL 2A drill core), with a review of Antarctic Oligocene and Neogene Pectinidae (Bivalvia). (10th September 2013) - Beu, Alan; Taviani, Marco; Sigwart, Julia
Abstract Retrotapes andrillorum sp. nov., Hiatella cf. arctica (Linnaeus, 1767), ?Yoldia sp. (internal mould) and six taxa of Pectinidae are reported from the Burdigalian section of the ANDRILL 2A core, drilled in McMurdo Sound, Ross Sea. The pectinids are Adamussium cf. jonkersi Quaglio et al., 2010, Antarctipecten gen. nov. alanbeui (Jonkers, 2003), Austrochlamys forticosta sp. nov., Austrochlamys cf. marisrossensis Jonkers, 2003, Ruthipecten gen. nov., sp. nov. (not named) and a fragmentary specimen representing an unnamed genus and species. In a revision of Antarctic Pectinidae, Austrochlamys Jonkers, 2003, Ruthipecten gen. nov. (proposed for Chlamys (Zygochlamys) tuftsensis Turner, 1967, reported only from Wright Valley and the Vestfold Hills, not present in ANDRILL 2A), Leoclunipecten gen. nov. (proposed for Austrochlamys gazdzickii Jonkers, 2003, reported only from Oligocene rocks of King George Island, not present in ANDRILL 2A) and the unnamed genus in ANDRILL 2A are assigned to subfamily Chlamydinae, tribe Chlamydini, whereas Adamussium Thiele, 1934 and Antarctipecten gen. nov. are assigned to subfamily Palliolinae, tribe Adamussiini. The diverse Pectinidae in ANDRILL 2A suggest sea temperatures roughly 5°C warmer than at present in the Ross Sea during Early Miocene time.